Cardiopulmonary rehabilitation for patients undergoing cardiac surgery after hospital discharge: Integrative review (Research, Society and Development, 2024)
Cardiovascular diseases are considered a public health problem responsible for a high mortality rate. Individuals with heart disease may undergo clinical and/or surgical treatments, with surgery being responsible for clinical and functional complications. One way to prevent these complications is through cardiopulmonary rehabilitation - CR starting in the ICU. The objective of the study was to gather evidence regarding CR in patients undergoing cardiac surgery in order to prevent or minimize post-hospital discharge complications. This is an integrative review of the literature, based on articles that investigated CR in patients undergoing cardiac surgery after hospital discharge. The research followed some recommendations from PRISMA and the PICO strategy. Five databases were used: PubMed, Scopus, Web of science, Lilacs and SciELO. The health science descriptors (DeCS/MeSH), created by BIREME: Thoracic Surgery, Cardiac Rehabilitation, Postoperative Care, Educational Technology, Cardiac Surgical Procedures, Physical Therapy Specialty, Exercise and Enhanced Recovery After Surgery. A total of 19,380 articles were found, of which 6 articles were chosen. Which showed an improvement in functional capacity and physical function when subjected to a protocol of aerobic exercises and active kinesiotherapy. CR showed faster improvement in functional capacity and quality of life in the short and long term. However, the results are still conflicting, which may be related to the intensity, series and adherence to the exercises, making it necessary for more studies and protocols to be developed in order to consolidate their long-term effects with more evidence.